Al-Hisbah Contextualization in the Business Competition Law in Indonesia - Zakiyah, Ninik; Prananingtyas, Paramita; Disemadi, Hari Sutra; Gubanov, Konstantin (Universitas Islam Negeri Raden Intan Lampung, 2019)
Supervision of market activities and competition in Islam has existed since the time of Prophet Muhammad PBUH and, at the same time, became a duty of an official called a muhtasib (supervisor). Al-Hisbah, as a controller institution for economic activities and market competition, aims to uphold the amar ma'ruf nahi munkar (commanding the good and forbidding the evil). Meanwhile, KPPU, as an independent institution, functions as a controller of the practice of monopolies and unfair business competition in Indonesia under the principle of economic democracy to support national economic development. This research uses the juridical-normative method with a historical and conceptual approach. Having compared the role of KPPU in supervising business competition to al-hisbah institution in Islam, this study finds out that KPPU, in general, is similar to al-hisbah on account that the substance and the values contained in al-hisbah have been embedded in KPPU especially in upholding amar ma'ruf nahi munkar in economic activities and business competition.